Manajemen Kepala Madrasah dalam Meningkatkan Kinerja Guru - Warisno, Andi; Mujtahidin, Mujtahidin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The purpose of this study was to identify and describe: The principal's management function in improving teacher performance. The research was conducted at MTs Mathla'ul Anwar Rejoagung, Tanjung Agung Village, Katibung District, South Lampung Regency. This type of research is qualitative and descriptive research, namely research that describes the function of principal management in improving the performance of MTs Mathla'ul Anwar Rejoagung teachers, Tanjung Agung Village, Katibung District, South Lampung Regency. Sources of data in this study are Primary Data, consisting of principals, vice principals, staff/employees, and teachers, and Secondary Data, obtained from library research and documentation. Data collection methods in this study were observation, interviews, and documentation. The data analysis method is carried out by data processing (selecting, classifying, concluding results, and making data reduction). The results of the study indicate that the principal has carried out the stages of the management function well, from the planning stage to the supervision (controlling), but in practice, sometimes experiences obstacles to the lack of teacher awareness of discipline in teaching. The teacher's ability to evaluate learning is not yet comprehensive. Some of them still lead to cognitive aspects and psychomotor aspects are not paid attention to. Good principal management can improve teacher performance in planning, implementation, and evaluation. This can be seen from the increase in teacher discipline in teaching. The learning tools owned by the teacher are getting better and more complete.